2017
DOI: 10.5430/jer.v3n2p51
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes and antimicrobial resistance of S. pneumoniae nasopharyngeal carriage in children from Cyprus: A country with relatively low coverage with the seven-valent pneumococcal conjugate vaccine

Abstract: S. pneumoniae may cause serious invasive infections mainly in children and elderly adults leading to significant morbidity and mortality. This report describes the circulating serotypes and antimicrobial resistance of S. pneumoniae colonizing the nasopharynx of Cypriot children in 2007-2008 when the immunization coverage of children was still relatively low. The study focused on children between 6 months to 5 years of age in the Nicosia district. A nasopharyngeal specimen was obtained from 402 children who vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This phenomenon is attributed to the significant decrease in the presence of pneumococcal serotypes included in the vaccine as many of these serotypes are characterized by significant resistance to antimicrobials [ 6 ]. As it has been shown in our published study, two of the most frequent serotypes colonizing Cypriot children, specifically 6B and 19F, are vaccine serotypes and demonstrated a high percentage of resistance to both penicillin and erythromycin [ 13 ]. In Cyprus, coverage with the PCV7 vaccine at the time of the study was relatively low [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is attributed to the significant decrease in the presence of pneumococcal serotypes included in the vaccine as many of these serotypes are characterized by significant resistance to antimicrobials [ 6 ]. As it has been shown in our published study, two of the most frequent serotypes colonizing Cypriot children, specifically 6B and 19F, are vaccine serotypes and demonstrated a high percentage of resistance to both penicillin and erythromycin [ 13 ]. In Cyprus, coverage with the PCV7 vaccine at the time of the study was relatively low [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the tri-annual survey performed in Cyprus by the Ministry of Health among children 17–24 months old in 2009, revealed full coverage by the PCV7 vaccine only in 37.5%, partial coverage in 42% and no vaccine coverage in 20.5% of children [ 12 ]. The susceptibility pattern and the circulating serotypes of S. pneumoniae isolated in Cypriot children have been reported elsewhere [ 13 ]. So far, no previous studies have been reported in Cyprus examining potential risk factors for colonization by pneumococcus in Cypriot children.…”
Section: Introductionmentioning
confidence: 99%